PACEMAKER IMPLANTATION IN A PATIENT WITH UPPER LIMB VENOUS OBSTRUCTION: A CASE REPORT - V.O. POVAROV; R.E. KALININ; N.D. MZHAVANADZE; I.A. SUCHKOV (Avicenna Tajik State Medical University, 2024)
Today, permanent cardiac pacing is the most effective way to correct bradyarrhythmia. Most pacemaker leads are implanted through the veins of the upper extremities. Common vein access involves either a cephalic vein cutdown or a puncture of the subclavian or axillary veins. Implantation of leads may become technically difficult or unfeasible if there is an anomaly in the structure of the veins or, more often, occlusion/stenosis of the veins of the upper extremities after thrombosis. The article presents It is illustrated with the case of a 75-year-old patient with indications for pacemaker implantation presented by the article. The first implantation attempt was unsuccessful: extensive occlusion of the left subclavian vein (SCV) and stenosis of the right SCV were detected. The venous obstruction was asymptomatic. The patient underwent venography and was diagnosed with up to 90% luminal narrowing of the right SCV. Percutaneous transluminal angioplasty of the right SCV was performed; the residual stenosis was 50%. Subsequently, a dual-chamber pacemaker was successfully implanted into the patient; the postoperative period was uneventful. The vein obstruction could be related to a history of malignant neoplasm of the uterus. A brief literature review of various types of vascular access for pacemaker implantation and alternative implantation options complements the case report.